2017
DOI: 10.1177/0271678x17707398
|View full text |Cite
|
Sign up to set email alerts
|

Implications of neurovascular uncoupling in functional magnetic resonance imaging (fMRI) of brain tumors

Abstract: Functional magnetic resonance imaging (fMRI) serves as a critical tool for presurgical mapping of eloquent cortex and changes in neurological function in patients diagnosed with brain tumors. However, the blood-oxygen-level-dependent (BOLD) contrast mechanism underlying fMRI assumes that neurovascular coupling remains intact during brain tumor progression, and that measured changes in cerebral blood flow (CBF) are correlated with neuronal function. Recent preclinical and clinical studies have demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 99 publications
(144 reference statements)
2
83
0
Order By: Relevance
“…Indeed, enlarged perivascular spaces have been observed in syringomyelia in human [43], and in animal models [16,20]. Perivascular spaces exist within the functional complex of actrocytes, pericytes, endothelia and smooth muscle cells known as the neurovascular unit [44]. The coupling of perivascular flow to cerebral blood flow has been suggested in the brain to be involved in the homeostasis of the neurovascular unit by allowing metabolic waste clearance, regulated by astroglial flux [45].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, enlarged perivascular spaces have been observed in syringomyelia in human [43], and in animal models [16,20]. Perivascular spaces exist within the functional complex of actrocytes, pericytes, endothelia and smooth muscle cells known as the neurovascular unit [44]. The coupling of perivascular flow to cerebral blood flow has been suggested in the brain to be involved in the homeostasis of the neurovascular unit by allowing metabolic waste clearance, regulated by astroglial flux [45].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the degree of coupling between other hemodynamic or non-hemodynamic variables could yield valuable insights into dysregulation of the TME. For example, in brain tumors, a coupling analysis between an indicator of neural activity such as fluorescence from a voltage sensitive dye 39 or a calcium indicator expressed in the neurons 40 and indicators of vascular function such as BV, BF or Hb sat , could reveal disruptions of the neurovascular unit 41,42 . Such an indicator could then be exploited as a biomarker of tumor grade, invasion, or functional restoration following therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we did not assess abnormalities in neurovascular coupling and/or cortical reorganization in the vicinity of brain tumors that may result in false negative findings. A recent review noted that even low‐grade brain tumors can exhibit abnormal neurovascular coupling (Pak et al, ). It has been suggested that breath‐hold cerebrovascular reactivity mapping constitutes an essential component of quality control analysis in clinical tfMRI, particularly when performed for presurgical mapping of eloquent cortex (Pillai & Mikulis, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in patients with brain tumors demonstrated only moderate group level rsfMRI versus tfMRI language network concordance with substantial subject‐level variability (Sair et al, ). Infiltration and abnormal neurovascular coupling, generally greater with higher tumor grade but also present in low‐grade gliomas (Pak et al, ), may compromise blood oxygenation level dependent (BOLD) contrast, both in rsfMRI and tfMRI (Hou et al, ; Jiang et al, ; Holodny et al, ; Agarwal et al, ).…”
Section: Introductionmentioning
confidence: 99%